Implementation of Project-Based Learning Strategies in Citizenship Education in Elementary Schools - Lestari, Adinda (International Journal of Students Education, 2024)
Effective education aims not only to improve students' cognitive abilities but also to hone their creativity. Creativity is the ability to think critically, innovatively, and creatively which is an important provision to face future challenges. The project-based learning model is one of the most effective strategies to improve students' creativity. By providing active, meaningful, and relevant learning experiences, PjBL helps students develop critical, innovative, and creative thinking skills that are essential for future success. For teachers, this model also offers the opportunity to become facilitators who support holistic learning. Stages in PjBL Determination of the Main Question or Problem Teachers and students formulate the problem that will be the focus of the project. Project Planning Students design steps to complete the project, including dividing tasks within the team. Investigation and Exploration Students collect data, conduct research, interviews, or observations to support project completion. Product or Solution Creation Students produce real products, such as reports, posters, videos, or simulations. Based on research conducted: Project-based learning is effective in improving elementary school students' understanding, involvement, and civic values. Challenges such as limited time, facilities, and inequality of student involvement need to be addressed to optimize results.